Relationship between air pollution exposure and insulin resistance in Chinese middle-aged and older populations: evidence from Chinese cohort - Liu, Ping; Zhang, Zhaoliang; Luo, MingZhong (Frontiers in Public Health, 2025)
AimsThis study aimed to determine the relationships between mixed exposure to six air pollutants, namely, particulate matter with an aerodynamic diameter of 2.5 micrometers or less (PM2.5), PM with an aerodynamic diameter of 10 micrometers or less (PM10), sulfur dioxide (SO2), nitrogen dioxide (NO2), cobalt (CO) and ozone (O3), and insulin resistance (IR) indices in Chinese middle-aged and older populations.MethodsA total of 2,219 participants from the China Health and Retirement Longitudinal Study (CHARLS), who are followed from 2011 to 2015, were included. Surface air pollutant concentration data were obtained from the China High Air Pollutants (CHAP) database. Multivariable linear regression analysis was used to examine the longitudinal associations between different air pollutants and various IR indices. Additionally, Bayesian kernel machine regression (BKMR), weighted quantile sum (WQS) regression, and quantile-based g computation (Qgcomp) were further utilized to assess the mixed effects of the six air pollutants.ResultsFully adjusted linear models revealed that increases in the levels of the six air pollutants (in μg/m3) were associated with higher triglyceride–glucose–body mass index (TyG-BMI; Beta = 0.027–0.128), triglyceride–glucose–waist circumference (TyG-WC; Beta = 0.155–0.674), and metabolic score for insulin resistance (METS-IR; Beta = 0.001–0.029) values during the four-year follow-up period. Further mixture analysis indicated that combined exposure to the six air pollutants had a significant cumulative effect on the increases in these three IR indices. Among the pollutants, NO2 and O3 were identified as the primary contributor to the cumulative effect. The result of mediation analysis supported the mediating role of BMI in the relationship between air pollution and IR (mediation proportion: 49.1%–93.5%). The results from both subgroup analysis and sensitivity analysis supported the detrimental effects of air pollution on IR.ConclusionBoth individual and mixed exposures to air pollution were significantly associated with IR in Chinese middle-aged and older individuals, with our study providing new evidence.